The Relationship between Consumers' Unethical Behavior and Customer Loyalty in a Retail Environment - Van Kenhove, Patrick (Journal of business ethics, 2003)
This paper investigates the relationship between two outcomes of relationship marketing – affective commitment and behavioral loyalty – and consumers' unethical behavior. The main objective of the study is to assess whether affective commitment and behavioral loyalty to a store translate into more ethical behavior towards that store, controlling for the variables of age, gender, and ethical beliefs. The study does not rely on a single measurement tool, but is based on ten months' panel data and three different mail surveys targeted at 359 Belgian households. The results provide support for our hypothesis that affective commitment is indeed negatively correlated with consumers' unethical behavior. The same conclusion could not be drawn for the relationship between behavioral loyalty and consumers' unethical behavior. No significant relationship was detected, not even in situations where affective commitment was high. The results hold major implications for retailing practice.